2020
DOI: 10.3389/fped.2019.00523
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Balance vs. Sagittal Profile in Adolescent Idiopathic Scoliosis, Are They Correlated?

Abstract: Background: Clinical evaluation of the postural balance in adolescent idiopathic scoliosis has been evaluated by coronal and sagittal parameters. The relationship between coronal and sagittal parameters has not been fully studied in adolescent idiopathic scoliosis. Objective: This study aimed to evaluate the relationship between coronal and sagittal parameters in idiopathic scoliosis. Methods: One hundred and three patients of Adolescent Idiopathic Scoliosis (AIS) were recruited. Radiographs were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
(14 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have reported differences in sagittal alignment and spinopelvic parameters in early onset scoliosis and AIS patients before spine surgery compared to healthy children. 33,34 Surgical correction with PSFI seeks to correct postural imbalances in coronal and sagittal planes, as these are related to poor functional balance in AIS 35 and in adolescents and adults a relationship between spinopelvic parameters and health-related quality of life was shown. 11,12,36 Pre-operative planning for deformity correction therefore requires an understanding of spinopelvic parameters in order to minimize degenerative changes in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported differences in sagittal alignment and spinopelvic parameters in early onset scoliosis and AIS patients before spine surgery compared to healthy children. 33,34 Surgical correction with PSFI seeks to correct postural imbalances in coronal and sagittal planes, as these are related to poor functional balance in AIS 35 and in adolescents and adults a relationship between spinopelvic parameters and health-related quality of life was shown. 11,12,36 Pre-operative planning for deformity correction therefore requires an understanding of spinopelvic parameters in order to minimize degenerative changes in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is a three-plane deformity of the spine 1 . It is the most common type of scoliosis, affecting 2–4% of adolescents, mainly involving children between 10 and 18 years of age 2 .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In an analysis of the relationship between coronal and sagittal deformities in AIS, Hu et al 27 found that SS had a significant negative correlation with the MTC. In another recent study examining the relationship between the coronal and sagittal profile in AIS patients using canonical correlation analysis, Ma et al 28 found a positive correlation between coronal and sagittal spinopelvic parameters. Hence, in order to avoid PSI, sagittal parameters should be considered in AIS correction surgery and in future studies, beyond the traditional considerations of coronal parameters and relative curve correction.…”
Section: Discussionmentioning
confidence: 99%